Change in carers' activities after the death of their partners - Rosenwax, Lorna; Malajczuk, S.; Ciccarelli, Marina (Springer-Berlin, 2013)
Purpose: When a person is dying and during bereavement, family members often put their lives on hold to provide full-time care. Meaningful activities may be curtailed or forgotten. This study described the activities that changed between pre- and post-caring, and what factors assisted carers to re-engage in activities 2 years following the death of their partners. Methods: A mixed methods design included a cross-sectional survey and face-to-face interviews. The study occurred in 2009 with 40 females that cared for a partner who had subsequently died of cancer 2 years previously. Engagement in community and other activities was determined through use of the Activity Card Sort–Australia and semi-structured interviews. The SF-36v2 measured physical and mental health status, and perceived social support was measured using the Multidimensional Scale of Perceived Social Support.Results: Most carers in our study were more engaged in household activities post-caring compared to their pre-caring activities, but had decreased social and leisure activities. Living as a single person meant they had taken on new roles and responsibilities. Leisure and social activities previously associated with subjective well-being and health were reduced or lost. Greater social support contributed to a higher retention of activities post-caring. Conclusions: Retention of activities could be facilitated by participation in community services, recreational groups and other support and interest groups, both during and after caring.